Civic Knowledge and Attitude towards Epilepsy in Croatia - Bagić, Dragan (2005)
Stigmatization is determined by socio-cultural specificities, and active effort is necessary to ease its burden. This study was aimed at assessing, for the first time, public attitude towards epilepsy in Croatia, and represents the initial step for a public health awareness campaign.